2002
DOI: 10.1242/dev.129.7.1583
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Snail family members highlights their ability to promote chick neural crest formation

Abstract: The Snail gene family of transcription factors plays crucial roles in different morphogenetic processes during the development of vertebrate and invertebrate embryos. In previous studies of function interference for one of the family members, Slug, we showed its involvement and neural crest formation in the chick embryo. Now we have carried out a series of gain-of-function experiments in which we show that Slug overexpression in the neural tube of the chick embryo induces an increase in neural crest production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Among the epigenetic and genetic modifications, excessive methylation of the E-cadherin promoter and transcriptional suppression are observed as major activities in most carcinomas (Yoshiura et al, 1995;Tamura et al, 2000;Cheng et al, 2001;Hajra et al, 2002). In addition, transcriptional repressors of the Snail zinc finger transcription factor family, such as Snail and Slug, play an essential role in the activation and induction of EMT, as this alters the expression patterns of EMT biomarkers in favor of the mesenchymal phenotype (LaBonne and Bronner-Fraser, 2000;del Barrio and Nieto, 2002;Nieto, 2002). Indeed, the inflammatory TME has been further shown to induce cancer initiation, and metastasis through stimulating the EMT process (Buhrmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the epigenetic and genetic modifications, excessive methylation of the E-cadherin promoter and transcriptional suppression are observed as major activities in most carcinomas (Yoshiura et al, 1995;Tamura et al, 2000;Cheng et al, 2001;Hajra et al, 2002). In addition, transcriptional repressors of the Snail zinc finger transcription factor family, such as Snail and Slug, play an essential role in the activation and induction of EMT, as this alters the expression patterns of EMT biomarkers in favor of the mesenchymal phenotype (LaBonne and Bronner-Fraser, 2000;del Barrio and Nieto, 2002;Nieto, 2002). Indeed, the inflammatory TME has been further shown to induce cancer initiation, and metastasis through stimulating the EMT process (Buhrmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although CNC cells are a multi-potent cell population, they are usually regarded as progenitors but not stem cells due to their limited developmental potential, despite the existence of a small portion of multi-potent cells (Baroffio et al, 1991;Morrison et al, 1999;Crane and Trainor, 2006). Whether the fates of CNC cells are determined before or after migration remains in debate (Noden, 1983;del Barrio and Nieto, 2002;Trainor et al, 2002). It was reported previously that the mouse odontogenic CNC cells migrate into the first pharyngeal arch only at the 10-12 somite stage, suggesting that the odontogenic progenitors are committed during the pre-migratory or migrating stages (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The process of NCC induction and specification is complex and requires a specific level of signaling by the BMP, Wnt, FGF, RA, Shh, and Notch/Delta pathways to establish a gene regulatory network that is crucial for determining NCC identity ( Villanueva et al, 2002 ; Monsoro-Burq et al, 2003 ; Wu et al, 2005 ; Theveneau and Mayor, 2012 ; Pla and Monsoro-Burq, 2018 ; Rogers and Nie, 2018 ; Prasad et al, 2019 ). During the early steps of NCC formation, these morphogen pathways work in concert with various NCC transcription factors (TFs) such as snai1 , snai2/slug , sox9 , and twist , to establish the neural plate border, regulate NCC specification, and subsequent NCC migration ( Aybar et al, 2003 ; del Barrio and Nieto, 2002 ; LaBonne and Bronner-Fraser, 1998 , 2000 ; Pla and Monsoro-Burq, 2018 ; Rogers and Nie, 2018 ; Spokony et al, 2002 ). As shown in the previous sections, we found that partial depletion of several 16p12.1-affected genes significantly impacted twist expression patterns and NCC migration in the PAs, and that these defects were not due to changes in NCC proliferation rates.…”
Section: Resultsmentioning
confidence: 99%